Paediatric inguinal herniotomy with and without exploration of inguinal canal - Uddin, S M Borhan; Wahed, Md Abdul; Rahman, Md Tahidur; Mohammad, Sakil; Alam , Md Touhid; Salahuddin, Md (Journal of Paediatric Surgeons of Bangladesh, 2019)
Paediatric inguinal herniotomy can be done with exploration of inguinal canal and without exploration of inguinal canal. The External Oblique Aponeurosis (EOA) should be closed if herniotomy was done by exploration of inguinal canal. On the other hand, herniotomy can be performed through superficial inguinal ring without exploration of inguinal canal; because superficial and deep inguinal ring were superimposed in pediatric patient. This prospective study was carried out in the department of Pediatric Surgery, M Abdur Rahim Medical College Hospital & other private hospitals in Dinajpur from July 2013 to June 2017.Total number of the patients were 180. Among them herniotomy were done without exploration (group A) of inguinal canal in 90 patients and with exploration (group B) in 90 patients. Age ranged from 1 month to 10 years in both groups. Mean time was taken to complete the operation were 23 minutes and 29 minutes in group A & group B respectively. Results were uneventful in 85 and 83 patients in group A & group B respectively. Superficial wound infection occurred in 01 in group A and 02 patients of group B. Scrotal swelling occurred in 04 and 05 patients in group A and group B respectively. No recurrence or death was occurred in both groups of patients. The overall outcome of inguinal herniotomy was found better in group A patients. So Pediatric inguinal herniotomy without exploration of inguinal canal could be a better option than that of conventional procedure. Journal of Paediatric Surgeons of Bangladesh (2017) Vol. 8 (2): 43-46